Warehouse Controlling System Menggunakan Node MCU ESP32 Dan Implementasi Python Sebagai Visualisasi Data Sensor Secara Real-Time - Rizhan Dwi Putra Herlambang; Missi Hikmatyar; Shinta Siti Sundari (Sekolah Tinggi Teknologi Wastukancana, 2025)
Warehouse management in large industries and SMEs (Small and Medium Enterprises) in Indonesia is a critical aspect that must be addressed seriously. Most warehouse systems still rely on manual processes, such as checking humidity, temperature, and gas levels in the storage area. This approach is inefficient as it requires significant time and manpower for regular monitoring. Manual operations using human resources have limitations in terms of labor, time efficiency, accuracy, and operational costs, such as employee wages. To address these challenges, this study proposes the development of an automated system based on the ESP32 microcontroller, which serves as a full controller, utilizing the DHT-11 sensor for temperature and humidity measurement, and the MQ-135 sensor for gas detection. Additionally, Python programming is implemented for data visualization, allowing real-time display on a laptop or computer to facilitate warehouse monitoring. The system developed is designed to read, control, and transmit sensor data. It can measure humidity, temperature, and gas concentration (PPM) and control actuators, such as a relay to activate a buzzer or light, according to the algorithm programmed into the ESP32. The results indicate that the system is capable of reading temperature and humidity with a data error rate of 6%, and gas concentration with an error rate of 2%. Additionally, the data transmission and visualization are functioning properly, in real-time